Students’ Perception on Learning Vocabulary through Watching Western Movies - Jihan Aulia Dwi Saputri; Dahniar, Dahniar; Halim, Nur Muthmainnah; Kamal, Alfiandy (English Literature Studi Program Universitas Islam Makassar, 2024)
This study aims to investigate students' perceptions of learning English through movies and explores the advantages of vocabulary acquisition via this medium. Utilizing qualitative methods, questionnaire responses from English Literature students from academic years 2019 to 2022 were gathered. Results reveal that students find learning English through movies to be enjoyable, effective, and engaging. They report benefits such as enhanced word spelling, contextual comprehension, and pronunciation skills. Despite encountering challenges, the use of movies as a learning tool remains effective. This research underscores the potential of incorporating movies into language learning curricula as it aligns with students' preferences and provides tangible benefits for vocabulary development